Stock Procurement and Documentation as Emergency Trolley Content Discrepancy Factors in Emergency Installation (Study on a Private General Hospital in Malang Regency) - Yoga Sedana, I Ketut; Listuhayu, Kararawi; Setijowati, Nanik (Fakultas Kedokteran Universitas Brawijaya, 2022)
One of the common problems in managing emergency logistics is the emergency trolley that conflicts with the standard operating procedures. It causes a mismatch of the emergency trolley contents. In fact, the availability of unstandardized emergency trolleys will impact the quality of emergency services in the emergency department. The emergency medicine shortage and emergency trolley content discrepancy also occurred several times in the ER. This study was conducted to analyze the determinant factor of content discrepancy in the emergency trolley in the emergency room of a private hospital in Malang Regency. The research method used was descriptive quantitative. The methods of identifying the root of the problem were carried out through field observations, literature studies, brainstorming, and Focus Group Discussions (FGD). Statistical tests were done using Bartlett's test of sphericity and Kaiser-Mayer Olkin (KMO) with a value higher or equivalent to 0.5. The study results formed two determinants of content discrepancies in the emergency trolley in the ER. The stock procurement factor is able to explain the problem by 48.02%, and the process documentation factor is able to explain the problem by 17.63%.